PERSPECTIVES FROM THE FIELD: Shale Energy Development—The "Other" Infrastructure. (21st June 2016) - Piner, Angela
Abstract : With the rapid pace of development in the various shale plays across the United States, there is a cultural change for the electric utilities occurring. Electric power infrastructure is being rapidly constructed to support shale development that requires environmental review that was rarely conducted in the past. Power generation and transmission lines are an important cog in the development of this infrastructure but not in the limelight when discussing shale energy development. This presentation will highlight some of these shale plays, the infrastructure being built in support of these plays, and the key environmental issues that may impact the pace of development. Environmental Practice 18: 125–128 (2016)